Cinnamaldehyde prevents intergenerational effect of paternal depression in mice via regulating GR/miR-190b/BDNF pathway - Gao Zhi-ying; Chen Tian-yu; Yu Ting-ting; Zhang Li-ping; Zhao Si-jie; Gu Xiao-yang; Pan Ying; Kong Ling-dong (Acta Pharmacologica Sinica, 2022)
Paternal stress exposure-induced high corticosterone (CORT) levels may contribute to depression in offspring. Clinical studies disclose the association of depressive symptoms in fathers with their adolescent offspring. However, there is limited information regarding the intervention for intergenerational inheritance of depression. In this study we evaluated the intervention of cinnamaldehyde, a major constituent of Chinese herb cinnamon bark, for intergenerational inheritance of depression in CORT- and CMS-induced mouse models of depression. Depressive-like behaviors were induced in male mice by injection of CORT (20 mg·kg−1·d−1, sc) for 6 weeks or by chronic mild stress (CMS) for 6 weeks. We showed that co-administration of cinnamaldehyde (10, 20, or 40 mg·kg−1·d−1, ig) for 6 weeks in F0 males prevented the depressive-like phenotypes of F1 male offspring. In addition, co-administration of cinnamaldehyde (20 mg·kg−1·d−1, ig) for 4 weeks significantly ameliorated depressive-like behaviors of chronic variable stress (CVS)-stimulated F1 offspring born to CMS mice. Notably, cinnamaldehyde had no reproductive toxicity, while positive drug fluoxetine showed remarkable reproductive toxicity. We revealed that CMS and CORT significantly reduced testis glucocorticoid receptor (GR) expression, and increased testis and sperm miR-190b expression in F0 depressive-like models. Moreover, pre-miR-190b expression was upregulated in testis of F0 males. The amount of GR on miR-190b promoter regions was decreased in testis of CORT-stimulated F0 males. Cinnamaldehyde administration reversed CORT-induced GR reduction in testis, miR-190b upregulation in testis and sperm, pre-miR-190b upregulation in testis, and the amount of GR on miR-190b promoter regions of F0 males. In miR-190b-transfected Neuro 2a (N2a) cells, we demonstrated that miR-190b might directly bind to the 3′-UTR of brain-derived neurotrophic factor (BDNF). In the hippocampus of F1 males of CORT- or CMS-induced depressive-like models, increased miR-190b expression was accompanied by reduced BDNF and GR, which were ameliorated by cinnamaldehyde. In conclusion, cinnamaldehyde is a potential intervening agent for intergenerational inheritance of depression, probably by regulating GR/miR-190b/BDNF pathway.